2022
DOI: 10.7759/cureus.21103
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Prevalence, Electroencephalogram (EEG), and Neuroimaging Correlation in Seizures Among Children in Odisha, India

Abstract: Background: Febrile seizures are very common in pediatric practice. We need to differentiate between febrile seizures and other seizures due to central nervous system (CNS) infection by various means of investigation. Though approximately 30% of patients with febrile seizure have later epilepsy and the risk is around 20% even if electroencephalogram (EEG), and neuro-imagings are normal. But data regarding this is laking in developing countries like India.Aim: The primary objective of this study is to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…It is found that those cases that had multiple focal convulsions are more likely to have abnormal MRI findings ( p = 0.002). Other studies have shown similar findings [ 11 , 17 , 18 ]. Further, in cases with the postictal deficit, 66.67% had abnormal MRI findings.…”
Section: Discussionsupporting
confidence: 83%
“…It is found that those cases that had multiple focal convulsions are more likely to have abnormal MRI findings ( p = 0.002). Other studies have shown similar findings [ 11 , 17 , 18 ]. Further, in cases with the postictal deficit, 66.67% had abnormal MRI findings.…”
Section: Discussionsupporting
confidence: 83%